Implementation of Lean Management to Improve the Operational Efficiency of Manufacturing Companies - Christ Windreis (Maneggio, 2025)
In the manufacturing industry, the implementation of Lean Management aims to improve efficiency and reduce waste at every step of the production process. A poor understanding of lean principles and resistance to change at the organizational level are two main issues in implementing Lean. This study aims to review various journals discussing the implementation of Lean Management in the manufacturing industry. National and international journals were used to search for academic articles, with archives from 2019 to 2024. The researcher collected 3 articles that discuss various aspects of Lean Management practices, such as waste reduction, improved production flow, and quality enhancement. The studies indicate that proper implementation of Lean Management can improve operational efficiency, reduce production costs, and enhance product quality. However, the implementation of lean requires management commitment and a supportive company culture. In conclusion, Lean Management can improve the performance of manufacturing industriesifsupported by thorough planning and continuoustraining.